Hopium or empowering hope? A meta-analysis of hope and climate engagement - Geiger, Nathaniel; Dwyer, Timothy; Swim, Janet K. (Frontiers in Psychology, 2023)
Researchers are increasingly examining whether hope can motivate action on climate change, or conversely, whether it might demotivate such action. We present a meta-analysis (k = 46) of quantitative studies examining the relationships between measures and manipulations of hope with climate engagement. On average, measured hope was associated with greater climate engagement (r = .18); however, this effect differed based on the target of hope. Hope regarding the possibility of respondents taking action was particularly strongly associated with greater engagement (r = .40), while in contrast, hope grounded in climate change not being a problem was associated with less engagement (r = -.40). Hope in response to climate change generally, and domain-general hope, were only weakly associated with greater engagement (rs = .13, .20). On average, hope manipulations fostered increased engagement, though the increase was small (Cohen’s d = .08). Subgroup analyses suggested two promising types of hope manipulations warranting future research: personal efficacy (k = 2, d = .18) and in-depth (k = 2, d = .49). In contrast, messages suggesting societal efficacy (i.e., providing a sense of possibility that climate change could be addressed) did not significantly or substantially boost (nor discourage) engagement (d = .05), and status quo-framed messages (i.e., messages highlighting that environmental conditions could stay the same if climate action is taken) had a marginally significant negative effect on engagement (d = -.18). After excluding a single outlier, the extent to which manipulations increased hope were not correlated with increases in climate engagement, suggesting the possibility that hope might be incidental to the success of some manipulations rather than a necessary component for promoting engagement. Overall, our meta-analysis does not suggest that increasing hope decreases climate engagement, with the possible exceptions of denial hope and status quo framed messages. Conversely, however, results provide partial yet inconclusive evidence for the hypothesis that increasing hope increases climate engagement. Given the existing published literature, we argue that future researchers should consider study designs that align with theoretical perspectives on how hope promotes climate engagement (e.g., longitudinal designs) and also consider directly assessing populations of interest (e.g., climate activists).